Factors Affecting Students Difficulties in Learning Geometry: A Qualitative Study - Manandhar, Dev Chandra (NPRC Journal of Multidisciplinary Research, 2026)
Background: Geometry plays a substantial role in developing students’ logical reasoning, spatial conception, and problem-solving skills. Many secondary-level students in Nepal have faced pressing problems in learning geometry. It has been found to result in low achievement and negative attitudes of those students toward the issue.Purpose: This study aims to explore the underlying factors that contribute to students’ difficulties in learning geometry and to identify effective strategies to enhance teaching geometry in the Nepalese context.Methods: To attain the objectives, I employed an exploratory research design which involved 10 semi-structured interviews and classroom observations of 24 students and 6 teachers from six public secondary schools in Makawanpur District, Nepal in 2025. Thematic analysis was used to interpret the data and identify key patterns of challenges and influences on geometry learning.Key findings: Students face cognitive challenges in understanding geometry concepts, affective barriers such as anxiety and low confidence hinder their learning, and instructional as well as contextual limitations negatively impact their academic performance.Implications: This study underscores the need for learner-centered, technology-supported teaching with continuous teacher training and equitable resources to create supportive classrooms that build students’ confidence and interest in geometry.